Selective etching method for customized preparation of MoS2 zigzag boundary

Molybdenum foil technology that regulates the precursor concentration and electrochemical oxidation treatment through the space-limiting method, selective etching of the zigzag edge of MoS2 is achieved, solving problems such as uncontrollable atomic terminals and material damage in the prior art, and improving the stability and repeatability of the process.

CN120210765APending Publication Date: 2025-06-27TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510365267.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The prior art is difficult to accurately control the sawtooth edge structure of two-dimensional transition metal disulfides (TMDs), resulting in problems such as uncontrollable atomic terminals, material damage, fluctuations in precursor concentrations and unclear etching mechanisms.

Method used

The precursor concentration is regulated by the spatial domain method, and the electrochemical oxidation treatment molybdenum foil is used as the molybdenum source to adjust the spacing between the molybdenum foil and the substrate, accurately control the local Mo/S ratio, and realize selective etching of the MoS2 zigzag edge.

Benefits of technology

Accurate control of Mo-zigzag and S-zigzag edges is achieved, the problems of uncontrollable atomic terminals and material damage are solved, the stability and repetition of the process are improved, and the quantitative relationship between the Mo/S ratio and edge stability during the etching process is verified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120210765A_ABST
    Figure CN120210765A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of two-dimensional material preparation, and particularly relates to a selective etching method for customized preparation of a MoS2 zigzag boundary. According to the method, the precursor concentration is regulated and controlled through a space limitation method, and selective etching of the double-layer molybdenum disulfide sawtooth-shaped edge is achieved. According to the method, molybdenum foil subjected to electrochemical oxidation treatment serves as a molybdenum source, the local Mo vapor concentration is accurately controlled by adjusting the distance between the Mo foil and a substrate, S-zigzag is etched preferentially in the Mo-rich environment, and Mo-zigzag is reserved; and synchronously etching the Mo-zigzag and the S-zigzag in an Mo lacking environment to form a mixed edge structure. The prepared MoS2Kigami structural material has the advantages of high crystal quality, low defect density and excellent electrical and optical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of two-dimensional material preparation, and more specifically relates to a selective etching method for customized preparation of MoS2 zigzag boundaries. Background Art

[0002] TMDs (two-dimensional transition metal dichalcogenides) have become ideal candidate materials for a new generation of optoelectronic, catalytic, and spintronic devices due to their unique electronic band structures (such as layer-dependent transitions from indirect to direct bandgaps) and diverse physical and chemical properties. Among them, the one-dimensional (1D) edges of TMDs (such as zigzag and armchair) exhibit distinct characteristics from the two-dimensional basal plane due to different atomic terminations (such as Mo-zigzag and S-zigzag). For example, zigzag edges have stronger nonlinear optical responses (Yu et al., 2024), higher catalytic activities (Qorbani et al., 2022), and magnetism (Chen et al., 2018). However, although CVD technology can already fabricate TMDs with different morphologies and layer numbers (Liu et al., 2022; Xia et al., 2023), precise control of their edge structures still faces significant challenges.

[0003] Traditional etching methods cannot balance the regulation of atomic edges and the high quality of crystals. Although plasma treatment and laser irradiation can generate structures with rich edges, there are irreversible damage problems. Although the regulation of hydrogen gas flow rate can achieve multi-stage etching (Geng et al., 2013), it cannot distinguish between Mo-zigzag and S-zigzag atomic terminations. The Jin team prepared a WSe2 Kirigami structure through a non-destructive chemical method, which avoided material damage but was difficult to regulate the atomic arrangement at the edges (Cai et al., 2018). These limitations stem from the sandwich crystal structure of TMDs (sulfur-metal-sulfur layers), whose edge atomic termination complexity far exceeds that of single-layer graphene, resulting in an unclear selective etching mechanism (Liu et al., 2022).

[0004] On the other hand, the uncontrollability of precursor concentration during the CVD growth process further exacerbates the difficulty of edge engineering. Traditional molybdenum sources (such as MoO3 powder) rapidly sublime at high temperatures, resulting in fluctuations in the local Mo / S ratio and making it difficult to stably adjust the edge growth rate (Xia et al., 2023). Although the Burton-Cabrera-Frank (BCF) theory indicates that the crystal morphology is dominated by the edge growth rate (Chen et al., 2021), there is still a lack of systematic research on how to precisely control the competitive growth or etching of Mo-zigzag and S-zigzag through precursor concentration in actual processes. For example, the literature reports that the S-zigzag edge rapidly disappears due to the binding of Mo atoms to the S-terminals in an environment with sufficient Mo (Chen et al., 2020), but there has been no breakthrough in how to stably achieve this process through experimental means.

[0005] It can be seen that the following core problems exist in the existing technologies:

[0006] Uncontrollable atomic terminals: Traditional etching cannot distinguish between Mo-zigzag and S-zigzag, resulting in a single-edge function;

[0007] Material damage: Plasma or laser introduces defects, restricting device performance;

[0008] Precursor concentration fluctuations: The rapid sublimation of MoO3 powder disrupts the process stability and affects repeatability;

[0009] Unclear mechanism: The quantitative relationship between the Mo / S ratio and edge stability during the etching process has not been established. Summary of the Invention

[0010] The purpose of the present invention is to provide a selective etching method for customized preparation of MoS2 zigzag boundaries, specifically a method for regulating precursor concentration through a spatial confinement method to achieve selective etching of the zigzag edges of bilayer MoS2.

[0011] To achieve the above purpose, the present invention provides the following solutions:

[0012] One of the technical solutions of the present invention: Provide a selective etching method for customized preparation of MoS2 zigzag boundaries, and the steps include:

[0013] The anodized molybdenum foil is used as a molybdenum source and placed above the substrate, the sulfur source is placed upstream of the substrate, and argon is used as a carrier gas. MoS2 Kirigami structural materials are obtained through chemical vapor deposition; by adjusting the distance between the molybdenum source and the substrate, an environment with sufficient Mo or insufficient Mo is provided to achieve selective etching for customized preparation of MoS2 zigzag boundaries.

[0014] Further, the steps of the anodic oxidation treatment include: electrochemically oxidizing for 400 s at a voltage of 0.51 V, wherein the electrolyte is a mixed solution of oxalic acid, sodium sulfate and sodium fluoride.

[0015] After the molybdenum foil is treated by anodic oxidation, a rich oxidation state is formed on the surface, from Mo 4+ to Mo 6+ , ensuring the stable release of Mo atoms. Electrochemical oxidation of the Mo foil provides a stable molybdenum source, avoiding uncontrollable etching caused by the high-temperature sublimation of MoO3 powder as a solid precursor for MoS2 growth.

[0016] Further, under the condition of sufficient Mo, the molybdenum foil is 3 - 5 mm away from the substrate.

[0017] Further, under the condition of insufficient Mo, the molybdenum foil is 5 - 10 mm away from the substrate, and the distance from the substrate is not 5 mm.

[0018] The present invention precisely controls the local Mo / S ratio by adjusting the distance between the molybdenum foil and the substrate, breaking through the limitation of traditional etching techniques that cannot distinguish atomic terminations. Combining atomic-scale characterization (HAADF-STEM) with DFT calculations, the energy stability of Mo-zigzag in a Mo-rich environment is verified.

[0019] Further, the sulfur source includes sulfur powder, thiourea or thioacetamide.

[0020] Optionally, the sulfur source is sulfur powder.

[0021] Further, the flow rate of argon is 60 sccm.

[0022] Further, the temperature of the chemical vapor deposition is 980 °C, the heating rate is 30 °C / min, and the time is 5 - 10 min.

[0023] During chemical vapor deposition, hexagonal star-shaped monolayer MoS2 is first grown on the substrate, and then hexagonal second-layer MoS2 is grown in the center of the first layer. At the same time, if the environment is a Mo-rich environment, Mo vapor is enriched in the space limited by the molybdenum foil and the substrate, and the S-zigzag edge is preferentially etched to form a Mo-zigzag structure (such as Figure 6 a - d), in a Mo-rich environment, excess Mo atoms combine with S terminations, accelerating the atomic desorption at the S-zigzag edge; if the environment is a Mo-deficient environment, the space limited by the molybdenum foil and the substrate is relatively large, resulting in the diffusion of Mo vapor and a decrease in the local Mo concentration, and the Mo-zigzag and S-zigzag are etched synchronously to form a mixed edge structure (such as Figure 6For e-h), when Mo is insufficient, the edge stability is verified by DFT calculations. The energy difference between Mo-zigzag and S-zigzag decreases, leading to synchronous etching, and thus achieving the purpose of selective etching by regulating the confined space.

[0024] The second technical solution of the present invention: Provide a MoS2 Kirigami structural material prepared by the above selective etching method.

[0025] The present invention is a method for regulating the precursor concentration by the space confinement method to achieve selective etching of the zigzag edges of bilayer molybdenum disulfide (MoS2). This method uses an electrochemically oxidized molybdenum foil (Mo foil) as the molybdenum source, precisely controls the local Mo vapor concentration by adjusting the distance between the Mo foil and the substrate, preferentially etches the sulfur-terminated zigzag edge (S-zigzag) in a Mo-rich environment, and retains the molybdenum-terminated zigzag edge (Mo-zigzag); in a Mo-deficient environment, Mo-zigzag and S-zigzag are etched synchronously to form a mixed edge structure. Combining experimental characterizations (such as aberration-corrected HAADF-STEM, Raman spectroscopy) with density functional theory (DFT) calculations verifies the effectiveness of atomic-level terminal control. The prepared MoS2 Kirigami structural material has high crystalline quality, low defect density, and excellent electrical and optical properties, providing a new strategy for two-dimensional material edge engineering and its applications in fields such as catalysis and optoelectronic devices.

[0026] The third technical solution of the present invention: Provide an application of the above MoS2 Kirigami structural material in catalysis and optoelectronic devices.

[0027] The present invention discloses the following technical effects:

[0028] The present invention precisely controls the distance between the Mo foil and the substrate, adjusts the local Mo / S atomic ratio, thereby selectively etching the Mo-zigzag or S-zigzag edge, solving the problem that traditional etching techniques cannot distinguish atomic terminals and are prone to damaging the material, and providing a new idea for the edge engineering of two-dimensional transition metal dichalcogenides (TMDs).

[0029] As the most common solid precursor for MoS2 growth, MoO3 powder has a rapid sublimation process during heating, which hinders the control of the precursor concentration. Therefore, the present invention uses an electrochemically oxidized Mo foil as the precursor to achieve continuous and stable supply of the Mo source. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation to the present invention. In the drawings:

[0031] Figure 1 Schematic diagram of selectively etching the bilayer MoS2 kirigami structure on the SiO2 / Si substrate.

[0032] Figure 2 Morphology image of the first-layer hexagonal star-shaped monolayer MoS2 grown on the substrate surface, where a-c are the morphology images corresponding to different positions on the substrate.

[0033] Figure 3 Morphology image of the second-layer MoS2 in the CVD growth and etching stage, a is the optical microscope image, and b is the scanning electron microscope image.

[0034] Figure 4 In a, it is a schematic diagram of the electrochemical oxidation treatment of the Mo foil, and b is the X-ray photoelectron spectrum of the Mo foil after electrochemical oxidation.

[0035] Figure 5 Schematic diagram of constructing a confined space by adjusting the distance between the Mo foil and the substrate.

[0036] Figure 6 Characterization images of the bilayer MoS2 prepared in Example 1 and Example 2. Among them, a is the optical microscope image of Example 1, b is the scanning electron microscope image of Example 1, c is the atomic force microscope image and its height profile of Example 1, d is the Raman mapping image of Example 1, e is the optical microscope image of Example 2, f is the scanning electron microscope image of Example 2, g is the atomic force microscope image and its height profile of Example 2, h is the Raman mapping image of Example 2, i is the Raman spectra of points 1, 2, and 3 in a, j is the photoluminescence spectra of points 1, 2, and 3 in a, and k is the XPS spectrum.

[0037] Figure 7 In a, it shows the atomic models of two kirigami structures, Mo-zigzag and S-zigzag. b is the SEM image of transferring the complete sample to the TEM grid by the wet transfer method. c is the selected area low-energy electron diffraction (SAED) image of the bilayer region. d is the high-angle annular dark-field HAADF-STEM image obtained from the monolayer (1L) region. e is the high-angle annular dark-field HAADF-STEM image obtained from the bilayer (2L) region. f is the intensity distribution diagram. g is the atomic resolution-level characterization of the unetched edge. h is the atomic resolution-level characterization of the etched region.

[0038] Figure 8 Stable configurations of MoS2 at different Mo and S concentrations. Among them, a-e are the atomic models of the Mo-zigzag structure at different Mo and S concentrations. f is the relationship diagram between the total energy and the Mo:S ratio. g is the relationship diagram between the average atomic energy and the Mo:S ratio.

[0039] Figure 9 In a, a schematic diagram of the principle of SHG (second harmonic generation) is shown; in b, an SHG mapping image; in c, a graph of the relationship between the SHG emission frequency and the incident frequency; in d, a graph of the SHG signal intensity under different excitation powers; in e, a graph of the relationship between the SHG intensity and the excitation power; in f, the results of polarized SHG measurement.

[0040] Figure 10 In a, a schematic diagram of a field-effect transistor (FET) based on a MoS2 kirigami structure is shown; in b, a curve of the drain current versus the drain voltage under different gate voltages; in c, a curve of the drain current versus the gate voltage under different drain voltages; in d-f, the results of optoelectronic performance tests under light sources of different wavelengths.

[0041] Figure 11 It is a characterization diagram of the etching degree for different CVD growth etching times. Among them, a is Example 1, b is Example 3, c is Example 2, and d is Example 4.

[0042] Figure 12 It is the cracking phenomenon that occurred during deposition at 1100°C in Comparative Example 1 and Example 2. Among them, a is Example 2 and b is Example 1. Detailed implementation manners

[0043] Now, various exemplary implementation manners of the present invention will be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, characteristics, and implementation schemes of the present invention.

[0044] It should be understood that the terms described in the present invention are only for describing specific implementation manners and are not used to limit the present invention. Additionally, for the numerical ranges in the present invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any intermediate value within any stated value or stated range, as well as each smaller range between any other stated value or intermediate value within the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0045] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention pertains. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein can also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In case of conflict with any incorporated document, the content of this specification shall prevail.

[0046] Without departing from the scope or spirit of the present invention, various modifications and variations can be made to the specific embodiments of the present invention specification, which are obvious to those skilled in the art. Other embodiments obtained from the present invention specification are obvious to those skilled in the art. The present invention specification and examples are merely exemplary.

[0047] Regarding the use of "comprising", "including", "having", "containing", etc. in this article, they are all open-ended terms, meaning including but not limited to.

[0048] It should be noted that the parts not described in detail in the present invention are all conventional operating means in the art and are not the focus of the present invention.

[0049] Example 1

[0050] Preparation of bilayer MoS2 with Mo-zigzag structure:

[0051] The Mo foil (0.002 inches thick) was electrochemically oxidized at 0.51 V for 400 seconds (electrolyte: a mixed solution of oxalic acid, sodium sulfate, and sodium fluoride, 9.45 g of oxalic acid, 7.1 g of sodium sulfate, and 0.21 g of sodium fluoride were configured into a 500 mL solution). The oxidized Mo foil was placed above the SiO2 / Si substrate with a spacing of 3 mm. Sulfur powder (150 mg) was placed upstream of the CVD furnace. The Ar flow rate was 60 sccm. After heating to 980 °C at a heating rate of 30 °C / min, sulfur vapor was introduced, and the CVD growth etching time was 5 min to obtain bilayer MoS2 with Mo-zigzag structure.

[0052] After introducing sulfur vapor, a hexagonal star-shaped monolayer MoS2 was grown on the substrate surface, and then a hexagonal second-layer MoS2 was grown at the center of the hexagonal star-shaped monolayer MoS2. Since the spacing between the Mo foil and the SiO2 / Si substrate was 3 mm, a Mo-rich environment was formed within the limited space between the two. Excessive Mo atoms combined with S terminals, accelerating the desorption of atoms at the S-zigzag edge, and thus forming a Mo-zigzag structure.

[0053] Example 2

[0054] Preparation of bilayer MoS2 with mixed edge structure:

[0055] Compared with Example 1, the only difference is that the oxidized Mo foil was placed above the SiO2 / Si substrate with a spacing of 6 mm.

[0056] At this spacing, under the limitation of the Mo foil and the substrate, a relatively Mo-deficient environment was formed. Due to the increase in space, the local Mo concentration decreased, and Mo-zigzag and S-zigzag were etched synchronously to form a mixed edge structure.

[0057] Example 3

[0058] Compared with Example 1, the only difference is that the CVD growth etching time is 10 min.

[0059] Example 4

[0060] Compared with Example 2, the only difference is that the CVD growth etching time is 10 min.

[0061] Comparative Example 1

[0062] Compared with Example 1, the only difference is that the temperature is raised to 1100 °C at a heating rate of 30 °C / min.

[0063] Comparative Example 2

[0064] Compared with Example 2, the only difference is that the temperature is raised to 1100 °C at a heating rate of 30 °C / min.

[0065] Test Example

[0066] Figure 1 It is a schematic diagram for selectively etching a bilayer MoS2 kirigami structure on a SiO2 / Si substrate. In the figure, the bilayer MoS2 is composed of a first hexagonal star-shaped layer and a second regular hexagonal layer. The S-zigzag edges are etched in an atmosphere rich in Mo, and the Mo / S-zigzag edges are etched in an atmosphere deficient in Mo.

[0067] Figure 2 It is a topographic map of the first hexagonal star-shaped monolayer MoS2 grown on the substrate surface. Among them, a-c are the topographic maps corresponding to different positions of the substrate. In the figure, it can be seen that the first layer of MoS2 in the initial growth stage is significantly different from the traditional triangular morphology. Based on this, different growth microenvironments are established by supplying different Mo concentrations during the etching stage, and the second layer shows different etching morphologies.

[0068] Figure 3 It is a topographic map of the second layer of MoS2 in the CVD growth etching stage (Example 1). a is an optical microscope image, and b is a scanning electron microscope image. In the figure, it is the second layer of MoS2 in the initial growth stage. The second layer of MoS2 structure is initially hexagonal, with alternating Mo-zigzag and S-zigzag edges, and is selectively etched in different atmospheres.

[0069] Figure 4 In it, a is a schematic diagram of the electrochemical oxidation treatment of the Mo foil, and b is the X-ray photoelectron spectrum of the Mo foil after electrochemical oxidation. In the figure, the X-ray photoelectron spectrum results confirm that the anodized Mo foil has a richer valence state (from IV to VI) than the MoO3 powder.

[0070] Figure 5 Schematic diagram for constructing a confined space by adjusting the distance between the molybdenum foil and the substrate. In the figure, it shows how to construct a confined space by adjusting the distance between the molybdenum foil and the substrate. Due to the limitation of high temperature and the instantaneous volatilization of the precursor, there are still challenges in accurately measuring the molar amount of the precursor. However, the macroscopic crystal morphology during the growth process can determine the quantitative ratio of the atoms participating in the reaction. Specifically, by controlling the length of the molybdenum foil, the vertical distance from the highest point to the substrate is controlled. When the distance is fixed between 3 - 5 mm (d1), multiple hexagonal crystal structures are observed. According to previous reports, this indicates that the ratio of S and Mo participating in the reaction is 2. As the reaction proceeds, the Mo foil can continuously and stably supply Mo atoms in the limited space, while a large amount of S powder is carried away by the carrier gas Ar, forming a Mo-rich microenvironment to achieve selective etching of the S zigzag edge. When the distance is adjusted between 5 - 10 mm (d2), the carrier gas will carry away more Mo atoms, resulting in a decrease in Mo concentration and a change in the etching behavior, that is, both the Mo-zigzag and S-zigzag edges are etched inward. Therefore, the concentration of the precursor can be regulated by adjusting the distance between the molybdenum foil and the substrate.

[0071] Figure 6 Characterization diagrams of the bilayer MoS2 prepared in Example 1 and Example 2. Among them, a is the optical microscope image of Example 1, b is the scanning electron microscope image of Example 1, c is the atomic force microscope image of Example 1 and its height profile, d is the Raman mapping image of Example 1, e is the optical microscope image of Example 2, f is the scanning electron microscope image of Example 2, g is the atomic force microscope image of Example 2 and its height profile, h is the Raman mapping image of Example 2, i is the Raman spectra of points 1, 2, and 3 in a, j is the photoluminescence spectra of points 1, 2, and 3 in a, and k is the XPS spectrum. In the figure, the optical microscope (OM) and scanning electron microscope (SEM) images clearly show two different kirigami structures, namely the Mo-zigzag structure ( Figure 6 in a and b) and the Mo / S-zigzag structure ( Figure 6 in e and f), both of which have richer edges than the traditional triangle. The atomic force microscope (AFM) confirms the bilayer characteristics of the etched structure. The inserted height profile confirms that the thickness of each layer is about 0.7 nm, corresponding to monolayer MoS2 ( Figure 6 in c and g). To study the quality of the MoS2 kirigami structure after etching, Raman and photoluminescence tests were carried out on the three points marked in Figure 6 a. Among them, the Raman results of points 1 and 2 show the same characteristic peaks, located at 381 cm -1 (in-plane vibration of Mo and S atoms, ) and 403 cm -1 (Out-of-plane vibrations of Mo and S atoms, A 1g ), and the displacement difference between the two peaks is about 22 cm -1 reveals the monolayer nature of the first layer and the etched region. The A of the second layer 1g and peaks have a slight red shift and blue shift respectively, and the displacement difference between these two peaks increases to 25 cm -1 , which is consistent with the characteristics of bilayer MoS2 ( Figure 6 i) in). and A 1g The frequency shifts of the modes can be attributed to the interlayer coupling and dielectric shielding effects. In bilayer MoS2, the van der Waals interaction between layers enhances the coupling of in-plane and out-of-plane vibrations, resulting in the decrease of the mode frequency and the increase of the A 1g mode frequency. Therefore, the peak spacing between these two modes expands significantly. For point 3, A 1g Raman peak mapping was performed to prove the uniformity of the kirigami structure, and the results showed clear boundaries, indicating a high quality of the etched sample ( Figure 6 d and h in). Figure 6 j in shows the photoluminescence spectra of three different regions (point 1, point 2, and point 3). A characteristic peak at 1.78 eV was detected in the spectra of the monolayer (point 1) and the etched region (point 2), corresponding to the A exciton of MoS2. The broad peak at 1.93 eV is related to the resonance of the B exciton. Points 1 and 2 exhibit similar intensities, both conforming to the characteristics of monolayer MoS2. In contrast, the intensities of both A and B excitons at point 3 decrease, and the intensity of the A exciton decreases more significantly because the bilayer region transitions from a direct bandgap to an indirect bandgap, resulting in a significant change in the energy band. The XPS core levels of Mo 3d have two peaks at 232.71 eV and 229.58 eV, corresponding to Mo3d 3 / 2 and Mo 3d 5 / 2 ( Figure 6 k in), and these peaks are consistent with the previously reported standard values without any peak shift, indicating that the etching did not affect the chemical environment of the atoms.

[0072] Figure 7Figure a shows the atomic models of two kirigami structures, Mo-zigzag and S-zigzag. Figure b is an SEM image of the complete sample transferred to a TEM grid by the wet transfer method. Figure c is a selected area low energy electron diffraction (SAED) image of the bilayer region. Figure d is a high angle annular dark field HAADF-STEM image obtained from the monolayer (1L) region. Figure e is a high angle annular dark field HAADF-STEM image obtained from the bilayer (2L) region. Figure f is an intensity distribution diagram. Figure g is an atomic resolution characterization of the unetched edge. Figure h is an atomic resolution characterization of the etched region. In the figure, atomic resolution HADDF-STEM is used to reveal the atomic arrangement, crystal quality, and stacking configuration of the kirigami structure. Figure 7 Figure b in it shows that the complete sample was successfully transferred to the TEM grid by the wet transfer method for subsequent observation of the atomic arrangement at the etched edge. The selected area low energy electron diffraction (SAED) image of the bilayer region ( Figure 7 Figure c in it) only contains a set of hexagonal diffraction spots, indicating the single crystal characteristics of the material and no twist angle appears. The high angle annular dark field HAADF-STEM images obtained from the monolayer and bilayer regions show a clear honeycomb structure ( Figure 7 Figures d and e in it), and the corresponding intensity distribution diagrams have similar intensities at each atomic column ( Figure 7 Figure f in it), indicating that MoS2 is in the 2H phase. The measured lattice spacings are 0.27 nm and 0.16 nm respectively, corresponding to the traditional MoS2 crystal planes (100) and (110). The unetched and etched edges were selected from the Mo-zigzag structure for atomic resolution characterization. The results show that the straight edge (unetched) terminates with Mo-zigzag ( Figure 7 Figure g in it), and the etched region terminates with S-zigzag ( Figure 7 Figure h in it), indicating that different atomic edges are selectively etched.

[0073] Figure 8 are the stable configurations of MoS2 at different Mo and S concentrations. Among them, Figures a - e are the atomic models of the Mo-zigzag structure at different Mo and S concentrations. Figure f is a graph of the total energy versus the Mo:S ratio. Figure g is a graph of the average atomic energy versus the Mo:S ratio. In the figure, first-principles calculations based on density functional theory (DFT) are used to further verify the experimental results and determine the stable configurations of MoS2 at different Mo and S concentrations. For different MoS2 boundary configurations, the growth environments of five Mo and S concentrations (0:2, 1:2, 2:2, 3:2, 5:2) were simulated, as Figure 8as shown in a - e of [reference]. The total energies of these systems were calculated in detail. It was found that in an Mo - deficient growth environment, the total energies of the Mo - zigzag S - zigzag structures were similar, indicating comparable stability between the two. As the Mo concentration increased, the total energies of these two structures began to diverge significantly, with the energy of the Mo - zigzag structure being lower and its stability being stronger (as shown in f of [reference]). Figure 8 as shown in [reference] Figure 8 as shown in g of [reference].

[0074] Figure 9 Figure a in [reference] shows a schematic diagram of the principle of SHG (second - harmonic generation), b is the SHG mapping image, c is the relationship diagram between the SHG emission frequency and the incident frequency, d is the SHG signal intensity diagram under different excitation powers, e is the relationship diagram between the SHG intensity and the excitation power, and f is the result of polarized SHG measurement. In the figure, SHG was used to characterize the quality and stacking phase of the etched kirigami structure. SHG signals can be observed in non - centrosymmetric structures (such as monolayer MoS2), but disappear in centrosymmetric structures (such as 2H - phase MoS2). The SHG mapping image shows that the intensity in the bilayer region is consistent with that of the SiO2 / Si substrate, and the SHG signal appears in the non - overlapping region of the monolayer region, indicating that the structure is of 2H - phase ( Figure 9 as shown in b of [reference]). The monolayer region without inversion symmetry has a significant SHG response. The SHG emission frequency in the monolayer region is twice the incident frequency ( Figure 9 as shown in c of [reference]). At the same time, at 532 nm, when the excitation power changes and the excitation wavelength is fixed at 1064 nm, different SHG signals are generated ( Figure 9 as shown in d of [reference]). Figure 9 Figure e in [reference] shows that the SHG intensity has a linear relationship with the excitation power, with a slope of 1.84, verifying the second - order nonlinear optical process. Further polarized SHG measurements were carried out on the monolayer region, confirming that the MoS2 kirigami structure prepared by this selective etching has a hexagonal lattice ( Figure 9 as shown in f of [reference]). In summary, the SHG behavior in different regions once again verifies the STEM result that the kirigami structure is 2H.

[0075] Figure 10Figure a shows a schematic diagram of a field-effect transistor (FET) based on the MoS2 kirigami structure. Figure b shows the relationship curve between the drain current and the drain voltage under different gate voltages. Figure c shows the relationship curve between the drain current and the gate voltage under different drain voltages. Figures d-f show the optoelectronic performance test results under light sources of different wavelengths. In the figure, the electrical transport characteristics of the MoS2 kirigami structure prepared by selective etching are shown. The fabricated field-effect transistor exhibits an on / off ratio of approximately 10 8 which is comparable to the reported values, indicating that the etching behavior does not damage the crystal quality, as shown in Figures a-b of Figure 10 . The optoelectronic performance under light sources of different wavelengths was further tested. As can be seen from Figures d-f of Figure 10 , the device exhibits the expected optoelectronic response in a wide wavelength range, and its off-current increases with the increase of the optical power.

[0076] Figure 11 Figures a-d are the characterization diagrams of the etching degree for different CVD growth etching times. Among them, Figure a is for Example 1, Figure b is for Example 3, Figure c is for Example 2, and Figure d is for Example 4. It can be seen from the figure that by adjusting the distance between the Mo foil and the substrate, two structures of Mo-zigzag and Mo / S-zigzag can be prepared. Meanwhile, as the reaction proceeds, the etching degree gradually deepens and continuously sinks towards the center.

[0077] Figure 12 Figures a-b show the cracking phenomenon that occurred during deposition at 1100 °C in Comparative Example 1 and Example 2. Among them, Figure a is for Example 2 and Figure b is for Example 1. It can be seen from the figure that the etching temperature should not be too high, otherwise cracks will appear and affect the sample quality.

[0078] The selectively etched bilayer MoS2 prepared by the method of the present invention directly observes the Mo-zigzag and S-zigzag terminations through aberration-corrected HAADF-STEM, with an edge resolution of 1 nm, demonstrating its atomic-level control. The high crystallinity of the prepared material is verified by various means including Raman, photoluminescence spectroscopy, SHG, and electrical transport characteristics. The etching only acts on the edge and has no impact on the internal quality of the material, indicating its high crystalline quality. Moreover, the success rate of fabricating the MoS2 kirigami structure exceeds 40%, indicating the high process repeatability of the present invention.

[0079] Its low sulfur vacancy density can enhance the edge activity and improve its catalytic effect.

[0080] The on / off ratio of its field-effect transistor (FET) reaches 10 8 , and the optical response covers 365 - 515 nm, which can be applied to the preparation of optoelectronic devices.

[0081] Its SHG response shows six-fold symmetry, is non-linear optically, and is suitable for photonic devices.

[0082] The various embodiments in this specification are described in a progressive manner. Each embodiment focuses on the differences from other embodiments. For the same and similar parts among the various embodiments, reference may be made to each other.

[0083] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be obvious to those skilled in the art. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown herein, but rather will be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A selective etching method for customized preparation of MoS2 sawtooth borders, characterized in that the steps include: Anodized molybdenum foil is placed above a substrate as a molybdenum source, a sulfur source is placed upstream of the substrate, and argon is used as a carrier gas to obtain MoS2 Kirigami structure material by chemical vapor deposition. By adjusting the distance between the molybdenum source and the substrate to provide a Mo-sufficient environment or a Mo-deficient environment, selective etching of customized preparation of MoS2 zigzag boundaries is achieved.

2. The selective etching method according to claim 1, characterized in that: The step of anodizing treatment includes: electrochemical oxidation at a voltage of 0.51 V for 400 seconds, wherein the electrolyte is a mixture of oxalic acid, sodium sulfate and sodium fluoride.

3. The selective etching method according to claim 1, characterized in that: Under the Mo sufficient environment condition, the molybdenum foil is 3-5 mm away from the substrate.

4. The selective etching method according to claim 1, characterized in that: Under the Mo-deficient environment, the molybdenum foil is 5-10 mm away from the substrate, and is not 5 mm away from the substrate.

5. The selective etching method according to claim 1, characterized in that: The sulfur source includes sulfur powder, thiourea or thioacetamide.

6. The selective etching method according to claim 1, characterized in that: The flow rate of the argon gas is 60 sccm.

7. The selective etching method according to claim 1, characterized in that: The temperature of the chemical vapor deposition is 980° C., the heating rate is 30° C. / min, and the time is 5-10 min.

8. A MoS2 Kirigami structural material prepared by the selective etching method according to any one of claims 1 to 7.

9. Use of the MoS2 Kirigami structure material according to claim 8 in catalysis and optoelectronic devices.